Assessing the relationship between Vocabulary Level Test (VLT) and reading comprehension - Alpino Susanto (Universitas Syiah Kuala, 2017)
It has been considered crucial about how vocabulary knowledge in relation with reading comprehension. This research was conducted to explore the link of Indonesian students Vocabulary Level Test (VLT) performance and their reading textbook on reading subject. Through this pilot research, it can describe the implications profile in English teaching process especially in reading. Furthermore it can give more information in how to measure the reading textbook reference for reading subject or other similar subject that involve reading activities. There were 30 undergraduate students in Universitas Putera Batam that participated in the VLT. Their English textbook (Mosaic 1) was profiled to measure the lexical vocabulary level. The results indicated that only 1% of the participants had mastered the 2000-word level which means the vocabulary textbook-level is still far from students vocabulary knowledge. From the level of comparison theoretically they would have difficulties to comprehend the reading textbook, and some additional activities would be recommended, before, during and after the reading subject.